2020
DOI: 10.3389/fonc.2020.564852
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Soft Tissue Sarcomas and Its Implications in Targeted Therapy

Abstract: Soft tissue sarcomas are a set of malignancies of mesenchymal origin. Due to the rarity and similarity in clinical presentation, they are grouped together and treated similarly in clinic. The response rates for current chemotherapy are around 20% and the median overall survival for advanced soft tissue sarcoma are less than 2 years. Thus, the current strategy with identical treatment for all soft tissue sarcomas is far from satisfactory. In this study, we first reviewed the current clinical and genomic finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
0
16
0
2
Order By: Relevance
“…Soft-tissue sarcomas (STS) are rare tumors of the connective tissues and account for 1% of all cancers (1). While the radiological assessment of STS typically includes size-based criteria, such as those defined by the Response Evaluation Criteria in Solid Tumors guidelines (RECIST 1.1) (2), intralesion heterogeneity is commonly seen in the clinic, both in tumor appearance and treatment response (3). Furthermore, several studies have reported that changes in tumor size have a poor correlation with histopathological tumor response (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Soft-tissue sarcomas (STS) are rare tumors of the connective tissues and account for 1% of all cancers (1). While the radiological assessment of STS typically includes size-based criteria, such as those defined by the Response Evaluation Criteria in Solid Tumors guidelines (RECIST 1.1) (2), intralesion heterogeneity is commonly seen in the clinic, both in tumor appearance and treatment response (3). Furthermore, several studies have reported that changes in tumor size have a poor correlation with histopathological tumor response (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Although surgery is considered the standard of care therapy, LMS tumors recur in over 80% of persons with LMS even after adequate resection. Persons with unresectable or recurrent LMS have limited systemic therapeutic options and display widely varying responses to therapy 1 3 . To date, there are no approved biomarkers of response in LMS that can be used to guide clinical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of patients with advanced STS is not ideal, and the median overall survival (OS) is less than 2 years. 9 And due to the heterogeneity of STSs, 2 patients who differ only in histological subtype may have very different prognoses. In addition, although the widely used American Joint Committee on Cancer (AJCC) TNM staging system represents the gold standard for classification system of STSs, criticisms of its limitations are still emerging.…”
Section: Introductionmentioning
confidence: 99%